2019
DOI: 10.2174/2213337206666190730144041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 7,3'-Epoxy-8,4'-Oxyneolignane-1’-Carboxylic Acid from Natural Eusiderin A and its Activity Against Trichophyton mentagrophytes

Abstract: Background: Eusiderin A is a neolignan derivate, which makes up the majority of the secondary metabolite of Eusideroxylon zwageri. It has been reported as a potent biopesticide and antifungal agent. Previous studies on the oxidation of terminal methylene of the allylic chain in Eusiderin A have been able to produce primary alcohol, pinacol, and an aldehyde which demonstrated strong activity against plant pathogenic fungi, therefore activity against dermal fungi needs to be studied. Objective: The current stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Positive results were dicided when the well showing no growth of bacteria (visually observed as clear solution), and it was determined as the MIC. 21 Based on Table 6, it can be concluded that MIC of the active fraction of Cassia fistula's bark against Propionibacterium acnes was 175 ppm, while that against Pseudomonas aeruginosa was 400 ppm.…”
Section: Minimum Inhibitory Concentration (Mic) and Minimum Bactericimentioning
confidence: 98%
“…Positive results were dicided when the well showing no growth of bacteria (visually observed as clear solution), and it was determined as the MIC. 21 Based on Table 6, it can be concluded that MIC of the active fraction of Cassia fistula's bark against Propionibacterium acnes was 175 ppm, while that against Pseudomonas aeruginosa was 400 ppm.…”
Section: Minimum Inhibitory Concentration (Mic) and Minimum Bactericimentioning
confidence: 98%
“…This polymer can prevent the release of drugs in saliva at pH 6.8 -7.4, on the other hand it will dissolve directly in stomach fluid at pH 1.0 -1.5. [26][27][28][29] Ethyl cellulose (EC) is a partly O-ethylated cellulose ether derivative. It is available in a variety of grades, which differ in viscosity, usually hydrophobic in nature and widely used in the biomedical and pharmaceutical industries.…”
Section: Thin Layer Chromatography (Tlc)mentioning
confidence: 99%
“…The effectiveness of the solvent evaporation method to produce microspheres depends on the successful entrapment of the active agent within the particles, and thus, this process is most successful with drugs which are either insoluble or poorly soluble in the aqueous medium which comprises the continuous phase. [27][28][29][30][31][32] There are different methods to prepare microparticles by solvent evaporation method. The choice of the method that will give rise to an efficient drug encapsulation depends on the hydrophilicity or the hydrophobicity of drug.…”
Section: Introductionmentioning
confidence: 99%
“…These effects were interconnected with secondary metabolites contained within. [1][2][3] There are four big metabolites group produced by Eusideroxylon zwageri. They are alkaloid, steroid, terpenoid and phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Microsporum gypseum is a fungus that causes skin diseases in humans. 3 Parts of human body that are often moist can easily be infected by pathogenic fungi. One of the most infectious pathogenic fungi is Microsporum gypseum which causes ringworm.…”
Section: Introductionmentioning
confidence: 99%